Cellular Responses of the Lichen Circinaria gyrosa in Mars-Like Conditions - de la Torre Noetzel, Rosa; Miller, Ana Z.; de la Rosa, José M.; Pacelli, Claudia; Onofri, Silvano; García Sancho, Leopoldo; Cubero, Beatriz; Lorek, Andreas; Wolter, David; de Vera, Jean P. (Frontiers in Microbiology, 2018)
Lichens are extremely resistant organisms that colonize harsh climatic areas, some of them defined as “Mars-analog sites”. There still remain many unsolved questions as to how lichens survive under such extreme conditions. Several studies have been performed to test the resistance of various lichen species under space and in simulated Mars-like conditions. The results led to the proposal that Circinaria gyrosa (Lecanoromycetes, Ascomycota) is one of the most durable astrobiological model lichens. However, although C. gyrosa has been exposed to Mars-like environmental conditions while in a latent state, it has not been exposed in its physiologically active mode. We hypothesize that the astrobiological test system “Circinaria gyrosa”, could be able to be physiologically active and to survive under Mars-like conditions in a simulation chamber, based on previous studies performed at dessicated-dormant stage under simulated Mars-like conditions, that showed a complete recover of the PSII activity (Sanchez et al., 2012). Epifluorescence and confocal laser scanning microscopy showed that living algal cells were more abundant in samples exposed to niche conditions, which simulated the conditions in micro-fissures and micro-caves close to the surface that have limited scattered or time-dependent light exposure, than in samples exposed to full UV radiation. The medulla was not structurally affected, suggesting that the niche exposure conditions did not disturb the lichen thalli structure and morphology as revealed by field emission scanning electron microscopy. In addition, changes in the lichen thalli chemical composition were determined by analytical pyrolysis. The chromatograms resulting from analytical pyrolysis at 500 ºC revealed that lichen samples exposed to niche conditions and full UV radiation consisted primarily of glycosidic compounds, lipids, and sterols, which are typical constituents of the cell walls. However, specific differences could be detected and used as markers of the UV-induced damage to the lichen membranes. Based on its viability responses after rehydration, our study shows that the test lichen survived the 30-day incubation in the Mars chamber particularly under niche conditions. However, the photobiont was not able to photosynthesize under the Mars-like conditions, which indicates that the surface of Mars is not a habitable place for C. gyrosa.